Relações de estudantes de letras com a leitura literária: entre leituras profissionais e comuns - Maura Maria dos Santos (2013)
The aim of this research was to analyze Letters students reading practices in order to understand their relationship with legitimate literature, recognized as such and traditionally privileged by academic institutions. The methodology was based on two combined data collection procedures: a questionnaire and an interview carried out in distinct stages. The first stage resulted in an exploratory study which started from a quantitative analysis of a sample of one hundred sixty nine questionnaires completed by undergraduate students of Letters at UFMG, Federal University of Minas Gerais. This stage led to a general sociological characterization of the sample, to the establishment of some correlations between the students interactions with their readings (whether or not linked to their Letters course) and to some data related to their social specificities and inclinations towards the course, the college,culture and reading. The second stage of the research aimed at a more profound appreciation of the findings and was based on the information gathered in interviews with twelve undergraduate students who were selected according to criteria established when the analysis of the data of the first stage was conducted. The research was based mainly in PierreBourdieus sociological studies, according to which the social origin and the specificities associated with the agents influence enormously the relationship between individuals and culture. Other scholars such as Philippe Coulangeon and Bernard Lahire, who develop the understanding of several factors determining the connections between social agents taste (or habitus), their positions in some social fields and their social practices, also complemented the theoretical basis of this study. The research findings showed firstly that the undergraduate students read canonical literature to some extent; secondly, the analysis of the interviews responses confirmed some common and some distinctive features in the readers profiles surveyed and also demonstrated significant influence of gender on the undergraduate students literature reading.